2020
DOI: 10.1126/science.aax6367
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for allosteric PARP-1 retention on DNA breaks

Abstract: The success of poly(ADP-ribose) polymerase–1 (PARP-1) inhibitors (PARPi) to treat cancer relates to their ability to trap PARP-1 at the site of a DNA break. Although different forms of PARPi all target the catalytic center of the enzyme, they have variable abilities to trap PARP-1. We found that several structurally distinct PARPi drive PARP-1 allostery to promote release from a DNA break. Other inhibitors drive allostery to retain PARP-1 on a DNA break. Further, we generated a new PARPi compound, converting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
247
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(266 citation statements)
references
References 53 publications
16
247
2
1
Order By: Relevance
“…We propose, therefore, that activation of PARP-1 is in all probability a two-step process, in which first DNA binding and then substrate binding contribute consecutively and additively to successive destabilisation of the folded structure of the HD subdomain, as summarised in Figure 6H. Previous work has shown that DNA binding also causes changes in the HD subdomain, with the strongest effects on NH solvent exchange seen for helices B, D and F ( Figure 1D) (16), while similar effects for EB-47 binding as reported here were found in a parallel HXMS study of allostery involving PARP inhibitors and their influence on the HD subdomain (58). Comparison of the crystal structures of the inhibitor complexes with that of the DNA-bound complex (4DQY) also shows differences, most notably that DNA binding causes helix F to become straight ( Figure 1J,K), whereas inhibitor binding, particularly of EB-47, has the opposite effect of increasing the bend in helix F, with movements in other helices, particularly E, that also differ between DNA and EB-47 binding ( Figures 6A-D).…”
Section: X-ray Crystal Structuressupporting
confidence: 81%
See 3 more Smart Citations
“…We propose, therefore, that activation of PARP-1 is in all probability a two-step process, in which first DNA binding and then substrate binding contribute consecutively and additively to successive destabilisation of the folded structure of the HD subdomain, as summarised in Figure 6H. Previous work has shown that DNA binding also causes changes in the HD subdomain, with the strongest effects on NH solvent exchange seen for helices B, D and F ( Figure 1D) (16), while similar effects for EB-47 binding as reported here were found in a parallel HXMS study of allostery involving PARP inhibitors and their influence on the HD subdomain (58). Comparison of the crystal structures of the inhibitor complexes with that of the DNA-bound complex (4DQY) also shows differences, most notably that DNA binding causes helix F to become straight ( Figure 1J,K), whereas inhibitor binding, particularly of EB-47, has the opposite effect of increasing the bend in helix F, with movements in other helices, particularly E, that also differ between DNA and EB-47 binding ( Figures 6A-D).…”
Section: X-ray Crystal Structuressupporting
confidence: 81%
“…Our data show that it is principally the slower conformational exchange processes, those detected by the NH solvent exchange experiments, that show differences amongst the WT protein, mutants and inhibitor complexes, whereas for the fastest processes, those detected mainly by the 15 shows very poor electron density and consistently high B factors throughout (58), while in solution,…”
Section: X-ray Crystal Structuresmentioning
confidence: 74%
See 2 more Smart Citations
“…Much recent work on analysing PARP1 has been stimulated by the discovery that inhibition of PARP activity results in synthetic lethality towards BRCA mutated cancer cells 8,9 . PARP inhibitors trap the protein at sites of DNA damage by inhibiting enzymatic activity and thereby block poly(ADP-ribose) induced unbinding [10][11][12][13] . This leads to increased double-strand breaks via collapse of replication forks 14,15 and confers sensitivity of BRCA mutated cells to PARP inhibitor drugs.…”
Section: Introductionmentioning
confidence: 99%